Building a Model for Refugee Rights Fulfillment: Community Collaboration at Cisarua Refugee Learning Centre in the Context of International Law - Arifin, Ridwan; Abidah , Shofriya Qonitatin; Qoiri, Mutmainah Nur; Nte , Ngboawaji Daniel; Ezzerouali, Souad; Chhachhar , Varun (Universitas Negeri Semarang, 2025)
This study explores the model of fulfilling refugee rights through community collaboration, with a specific focus on the Cisarua Refugee Learning Centre (CRLC) in Indonesia. Refugees, as one of the most vulnerable groups globally, often face significant challenges in accessing their basic rights, including education, healthcare, and legal protection. The research analyzes how community-based initiatives, especially through the CRLC, contribute to the realization of refugee rights in the context of international law, such as the 1951 Refugee Convention. This study emphasizes the importance of collaboration between refugees, local communities, and international organizations in fostering an inclusive environment for refugees to access essential services. By examining the CRLC's efforts in providing education, skills, and advocacy for refugees, this paper proposes a sustainable model for refugee rights fulfillment that aligns with international legal standards.